Stellaluna - Cannon, Janell (Harcourt brace and company, 1993)
Stellaluna is the tender story of a lost young bat who finally finds her way safely home to her mother and friends. Knocked from her mother's safe embrace by an attacking owl, Stellaluna lands headfirst in a bird's nest. This adorable baby fruit bat's world is literally turned upside down when she is adopted by the occupants of the nest and adapts to their peculiar bird habits.